ANALISIS SISTEM INFORMASI AKUNTANSI TERHADAP PENERIMAAN KAS PADA BANK TABUNGAN NEGARA (PERSERO) TBK KC. MEDAN - Ade Suriani Lubis; Bella Sapira; Ahmad Aidil Siregar; Ova Novi Irama (Sekolah Tinggi Pariwisata Mataram, 2022)
Cash is one of the most important things for a company to manage a company well. One way of managing cash is through implementing a revenue accounting information system. This study aims to analyze the cash receipts system at the State Savings Bank Kc. Medan. The object of this research is the cash receipts accounting system at the State Savings Bank Kc Medan. This research method uses descriptive analysis. The results of research at the State Savings Bank Kc. Medan shows that the cash receipt system does not operate effectively and there is no good internal control system.